Antimicrobial activity and phytochemical screening of branches, fruits and leaves of Eugenia brejoensis - de Azevedo, Priscila Roberta; Nascimento da Silva, Luís Cláudio; Gomes-Silva, Alexandre; Macedo, Alexandre José; de Araújo, Janete Magali; Silva, Marcia Vanusa (Scientia Plena, 2012)
Cyclohexane, Ethyl acetate and n-butanol fractions obtained from a liquid-liquid partition of methanolic extract from E. brejoensis leaves, fruits and branches. All tested tissue showed antimicrobial action. The leaves showed the best results. Polyphenols, flavanoids and tannin are related as possible active compounds. Our results show at the first time the broad spectrum antimicrobial activity of E. brejoensis, an endemic Caatinga plant. The isolation and structural characterization of these antimicrobial compounds is a sustainable application of the natural resource from Caatinga biome.